Development of Hydro-Meteorological Hazard Early Warning System in Indonesia - Susandi, Armi; Tamamadin, Mamad; Pratama, Alvin; Faisal, Irvan; Wijaya, Aristyo R.; Pratama, Angga F.; Pandini, Olgha P.; Widiawan, Destika Agustina (ITB Journal Publisher, LPPM ITB, 2018)
This paper discusses the result of the development of a hydro-meteorological hazard early warning system (H-MHEWS) that combines weather prediction from Weather Research and Forecasting (WRF) and the hydrometeorological hazard index from the National Disaster Management Authority (BNPB), Indonesia. In its current development phase, the hazards that H-MHEWS predicts are floods, landslides, and extreme weather events. Potential hazard indices are obtained by using an overlay approach and resampling so that the data have a 100-m spatial resolution. All indices are classified into 4 status categories: âNo alertâ, âAdvisoryâ, âWatchâ, and âWarningâ. Flood potential is produced by overlaying rainfall prediction at 3-hour intervals with the flood index. Landslide potential is produced by overlaying rainfall prediction with the landslide index. Extreme weather potential is divided into 3 categories, i.e. heavy rain, strong winds, and extreme ocean waves. The whole prediction is dynamic, following weather predictions at 3-hour intervals. The hazard prediction results will trigger a âWarningâ alert in case of emergency status. This alert will be set up in a notification system to make it easier for the user to identify the most dangerous hydrometeorological hazard events.